Identification of a major QTL and candidate genes analysis for branch angle in rapeseed (Brassica napus L.) using QTL-seq and RNA-seq - Lei, Shaolin; Chen, Li; Liang, Fenghao; Zhang, Yuling; Zhang, Chao; Xiao, Huagui; Tang, Rong; Yang, Bin; Wang, Lulu; Jiang, Huanhuan (Frontiers in Plant Science, 2024)
Branching angle is an essential trait in determining the planting density of rapeseed (Brassica napus L.) and hence the yield per unit area. However, the mechanism of branching angle formation in rapeseed is not well understood. In this study, two rapeseed germplasm with extreme branching angles were used to construct an F2 segregating population, and a branching angle-associated quantitative trait loci (QTL) was mapped on chromosome C3 (C3: 1.54-2.65 Mb) by combining bulked segregant analysis sequencing (BSA-seq) as well as traditional QTL mapping. A total of 54 genes had SNP/Indel variants within the QTL interval were identified. Further, transcriptome sequencing (RNA-seq) of the two parents revealed that 12 of the 54 genes were differentially expressed between the two parents. Finally, we further validated the differentially expressed genes using qPCR and found that six of them presented consistent differential expression in all small branching angle samples and large branching angles, and thus were considered as candidate genes related to branching angles in rapeseed. Our results introduce new candidate genes for the regulation of branching angle formation in rapeseed, and provide an important reference for the subsequent exploration of its formation mechanism.